(untitled) (INTERNATIONAL JOURNAL OF APPLIED SCIENCE & TECHNOLOGY, 2019)
Superplasticizer or high-range water reducer is a specific type of admixtures that is used to produce low water-cement ratio high-strength concrete with normal or enhanced workability. Therefore, by using superplasticizers, it became easier for contractors nowadays to place highly workable, durable, pumpable concretewith higherstrength, and evenwith less cost than using otherwaysto produceconcretewith such properties. The effects of superplasticizers on physical properties of hardened and fresh concrete have been studied in this paper by using different dosages of superplasticizer. The compressive strength tests were conducted for concrete samples of different dosages at 7 days and 28 days to determine the properties of hardened concrete, while the slump tests were conducted to determine the properties of fresh concrete as well. The results show that thehighest compressive strength at 28 days was achieved at 3% dosage of superplasticizer, while the highest compressive strength at 7days achieved at 1% dosage. Whereas, using higher dosage of superplasticizer resulted in a lower compressive strength with very high slump value